Towards a CubeSat relevant mission payload for demonstrating aspects of In-Situ ResourceUutilisation (ISRU) on a C-type Near-Earth Asteroid (NEA) - Chindo, Aminu Musa (Cranfield University, 2022)
Nearly 50 years ago, humankind long dreamed of colonizing or exploiting the neighbouring planets Mars, the Moon, comets, and asteroids in our Solar System for technological and profit-oriented purposes. The concept of In-Situ Resource Utilisation (ISRU) is likely to be a means to achieving those dreams. High cost and the possibilities of failure associated with the development of full-size ISRU spacecraft, early use of CubeSat payloads for ISRU technology demonstration would serve as a technology readiness level (TRL) driver and a de-risking technology. Mars Oxygen In-Situ Resource Utilization Experiment (MOXIE) is the only small size ISRU demonstration payload currently flown and on Mars to demonstrate oxygen extraction from the Martian atmosphere. The regolith/soils present in smaller bodies are identified to be rich in minerals resources such as precious metals, volatiles, organic and non-organic materials that can be harnessed for the good of humankind. This PhD research work aimed to advance an initial CubeSat-like payload design to demonstrate an ISRU process on a C – type near-earth asteroid (NEA). The result of the literature review performed was, the project background was elaborated. From the trade-off studies carried out for the selection process of the potential destinations and the ISRU process, C-type NEA 162173 Ryugu JU3, and hydrometallurgical sulphuric acid leaching experiment on olivine minerals have emerged as the winners. System requirements are generated, and for the proposed CubeSat payload system architecture comprising of sample acquisition subsystem, reaction chamber subsystems, acid solution delivery and extraction subsystem, the electroplating/wining subsystem, and analytical subsystem, an initial overall payload system design was achieved. This project has been focused on the re-design and manufacturing of the reaction chamber subsystems and top- plate system, and the design and manufacture of the leaching and the liquid handling sub-system (LHS). The result of laboratory hydrometallurgical sulphuric acid leaching experiments carried out found the optimal condition to achieve higher metal extraction from the reaction mixture occurs at 5M H₂SO₄ acid concentration, 1:5 mineral to acid volume ratio (1g/5ml), and in a state of agitation. The inclusion of bromophenol blue (BPB) dye in the leaching experiment to eliminate the initial use of litmus paper, detect the loss of acid concentration by providing a real-time visual colour transition from yellow to blue, within the required acid pH range and would expect to be compatible with future flight implementation. Using the 5M H₂SO₄ acid concentration, the BPB dye solution was observed to degrade and change to colourless. Sourcing an alternative dye that is stable in 5M H₂SO₄ acid to mitigate against this looming challenge was suggested for future work. The payload system design together with the optimal leaching condition generated, informed the Breadboard (BB) payload prototype system design, component selection, and manufacture. A version of the Reaction Chamber Subsystem (RCS) oven implemented in a co- running CubeSat relevant payload design (ISRU water extraction), and based on the initial size and volume, appears to be suitable for this project. The RCS is manufactured from a material that is sulphuric acid-resistant and was re-designed to allow for interfacing to the LHS. The top plate implemented on CubeSat based ISRU water extraction project was adapted, re-designed, and manufactured from a material that is sulphuric acid-resistant to enable the accommodation of the LHS and the associated system that will ensure efficient interaction between acid solution and the collected olivine regolith. The LHS subsystem is comprised of valves, pumps, manifolds, reservoirs, tubing connectors, and fittings. These components are interconnected, and they interact to establish the LHS that will allow for efficient liquid handling in microgravity. The LHS is operated to deliver H₂SO₄acid solution from the reservoir into the RCS and the extraction of the leachate from the RCS respectively. In the conclusion, the manufactured BB payload system was operated to simulate hydrometallurgical leaching and aspects of liquid handling processes. The result indicates the usefulness of the process and its feasibility for CubeSat implementation. Additional tests need to be performed to further validate the BB payload system’s usefulness. Also, various future works are presented that will increase the technology readiness level of the design concept to further validate the usefulness of the ISRU BB payload system.
Keywords: CubeSat; ISRU; Hydrometallurgy; NEA; Ryugu; Leaching; Extraction